SOCIAL CONNECTION DURING COVID-19: THE EXPERIENCES OF FIRST- AND CONTINUING-GENERATION UNIVERSITY STUDENTS (Proceedings of the Global Public Health Conference, 2022)
The COVID-19 pandemic and associated mitigation efforts (e.g., remote instruction) have significantly altered the higher education landscape. Since the onset of the pandemic, undergraduate enrollment has declined, particularly at public four-year universities and among first-generation students. Consequently, it is essential for researchers, administrators, counselors, faculty, and other higher education stakeholders to understand the impact of the pandemic on students (particularly first-generation students in the public university sector), as well as what resources are needed to address this impact. We explored social support, interpersonal connection, and relationship loss among university students during the first 12 months of the COVID-19 pandemic, and whether those experiences differed as a function of generation status. Data were collected as part of the COVID-19 University Research on Education and Sustainability (CURES) Project, a multi-site study of adjustment and resilience among college students during the COVID-19 pandemic. Undergraduate students (N = 395) completed the Three-Item Loneliness Scale and the NIH Adult Social Relationships Scale and reported whether they had experienced the ending of any close relationship(s) during the pandemic. Only half of students reported access to emotional and instrumental social supports; two-thirds reported feeling isolated, disconnected, and left out; and about half reported having lost a close relationship. First- and continuing-generation students did not differ on these variables. Access to a supportive social network and involvement in enduring, intimate relationships are both strongly related to optimal health and well-being; thus, our results are concerning. There may be creative ways, however, for institutional stakeholders to build feelings of community and social connection among their student population.
Keywords: COVID-19; student outcomes; social connection; relationships; pandemic